The Modern Approaches to Teaching Portions and Fractions in Primary Schools Mathematics - Mexriddinovna, Raximova Nargiza (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the issues of increasing the effectiveness of students' participation in mathematics lessons using information technology, the formation and strengthening of their knowledge and skills in modern technology.